Comparación de lima rotatoria y reciprocante en la modificación del ángulo en conductos curvos según el método de Schneider, 2021 - Vargas Ipanama, Karl (2022)
The objective of the research was to compare a rotary system and a reciprocating system in the modification of the angle in curved ducts according to the Schneider method, 2021. The type of research was quantitative, the design was non-experimental, comparative descriptive, cross-sectional. The study was performed on 40 mesiobuccal canals of permanent mandibular first molars randomly assigned to either of the 2 groups, Mtwo rotary file; Reciproc Blue reciprocating file (20 teeth for each group). The instrument used was the data collection sheet for the angle of curvature of curved ducts. The most important results were: The average curvature angle of the group to be instrumented with Mtwo changed 1.7º; before instrumentation it was 28.25º and after it was 26.55º. The average curvature angle of the group to be instrumented with Reciproc blue changed 1.25º; before instrumentation it was 25.6º and after it was 24.35º. In the group to be instrumented with Mtwo, moderate curvature was 25%: severe was 75%; after instrumentation moderate curvature was 35%: severe was 65%. In the Reciproc blue group the slight curvature was 5%; moderate 40% and severe 55%; after instrumentation did not change. There is a significant difference between the angle of the curvature before and after the instrumentation with Mtwo (p=0.000). There is a significant difference between the angle of curvature before and after instrumentation with Reciproc blue (p=0.000).